THE ANALYSIS OF THE NORTH BALI DIALECT IN THE PUJA ASTAWA’S VIDEO GARA-GARA DON POH MAU BUNUH ORANG - Agung Krsna Lila Dasa; Luh Putu Artini; Luh Putu Eka Sulistia Dewi (Undiksha Press, 2023)
This study aimed to describe one of the language variations, namely dialect in social interaction, in the YouTube video entitled “gara gara don poh mau bunuh orang” and to describe the choice of language in social interaction. This study uses a qualitative research approach. This study uses ethnographic research to examine the social behavior of language and community communication and how language is applied based on related cultural concepts. The dialect used in the video is the Buleleng (North Bali) dialect. The choice of language used is transfer code and code mix. For accents, this video uses a Buleleng accent because in the video, there are many words typical of north Bali that have the characteristics of swear words. For syntax, some sentences have affixes that refer to the subject, there are words that are in the sentence but do not change the meaning of the sentence, and there are also structures that are commonly used in the video. Keywords: sociolinguistics interaction, dialect, accent, concept, code mix